Downregulation of TET1 Promotes Glioma Cell Proliferation and Invasion by Targeting Wnt/β-Catenin Pathway - Jianwen Ji; Qiuxiang You; Jidong Zhang; Yutao Wang; Jing Cheng; Xiangyun Huang; Yundong Zhang (Analytical Cellular Pathology)
Glioma is the most common malignant tumor in adult brain characteristic with poor prognosis and low survival rate. Despite the application of advanced surgery, chemotherapy, and radiotherapy, the patients with glioma suffer poor treatment effects due to the complex molecular mechanisms of pathological process. In this paper, we conducted the experiments to prove the critical roles TET1 played in glioma and explored the downstream targets of TET1 in order to provide a novel theoretical basis for clinical glioma therapy. RT-qPCR was adopted to detect the RNA level of TET1 and β-catenin; Western blot was taken to determine the expression of proteins. CCK8 assay was used to detect the proliferation of glioma cells. Flow cytometry was used to test cell apoptosis and distribution of cell cycle. To detect the migration and invasion of glioma cells, wound healing assay and Transwell were performed. It was found that downregulation of TET1 could promote the proliferation migration and invasion of glioma cells and the concomitant upregulation of β-catenin, and its downstream targets like cyclinD1 and c-myc were observed. The further rescue experiments were performed, wherein downregulation of β-catenin markedly decreases glioma cell proliferation in vitro and in vivo. This study confirmed the tumor suppressive function of TET1 and illustrated the underlying molecular mechanisms regulated by TET1 in glioma.